Psychological Characteristics of Children and Adolescents with Conduct Disorder - Radulović, Danka M.; Radovanović, Dobrivoje (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
Conduct disorder is one of the most frequently diagnosis among delinquents, so prevention of this disorder is one of the prior task in the effort to reduce crime. However, difficulties with this plan arise even on the diagnostic level because behavioural criteria in DSM-IV do not enable precise differentiation between children and adolescents whose antisocial behaviour is transient and those whose behaviour is the result of some psychological characteristics and takes the risk of becoming chronic through juvenile delinquency and adult criminality. Nevertheless, DSM-IV declaire that we put diagnosis of conduct disorder only when in basis of symptomatical behavior lay disfunction inside individual and we do not put it when it is simply reaction on actually social context, in fact we have not any directions which will nearly determine the nature and contents of "disfunctions inside personality" nor it is mentioned any method that we could employ to identify it. The fact that we can put this diagnosis only when the foundation of conduct disorder is deeply embedded in the individual makes a psychological clinical approach necessary in the diagnostic procedure and in estimating the prognostic importance of this disorder. Deep exploration of juvenile personality with conduct disorder using the Rorschach test and big sample demonstrate certain disfunctions in structure and dynamic of children and adolescents which is almost in accordance with descriptions of the construct that many psychology of crime have conceptualized as early psychopathy (Hare, 1993), fledging psychopathy (Lynnam, 1966), early emotional frustration (Rygaard, 1998) etc.